Polar bear, Polar bear, what do you hear? - Bill, Martin (Mexico : Henry Holt, 1991)
Zoo animals from polar bear to walrus make their distinctive sounds for each other, while children imitate the sounds for the zookeeper.
Keywords: Animals sounds -- fiction; Zoo Animals -- fiction